2012
DOI: 10.4236/ajps.2012.36095
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization of <i>Hibiscus rosa-sinensis</i> L. Vegetative Explants Sourced from Plants Grown in Open Environment and Influences of Organic Ingredients on <i>In Vitro</i> Direct Regeneration

Abstract: This paper reports on the effects of organic ingredients in facilitating direct shoot regeneration from nodal explants of Hibiscus rosa-sinensis L. This paper also compares the sterilization conditions for 3 types of explants (node, internode, and shoot tip) harvested from an open field. The optimized sterilization conditions for the explants were 40% Clorox-20 min exposure, 10% Clorox-15 min exposure, and 5% Clorox-40 min exposure for the node, internode and shoot tip, respectively. In the direct shoot regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This can be related to the results of the present study, where the selection of in vitro explants decreased the chances of contamination, which subsequently increased the overall response of mung bean cultures. Shoots and internodes are already considered as better explants (Dar et al, 2012 ). Similarly, Himabindu et al ( 2014 ) developed an effective method to increase shoot multiplication in the green gram culture using cotyledonary nodes.…”
Section: Discussionmentioning
confidence: 99%
“…This can be related to the results of the present study, where the selection of in vitro explants decreased the chances of contamination, which subsequently increased the overall response of mung bean cultures. Shoots and internodes are already considered as better explants (Dar et al, 2012 ). Similarly, Himabindu et al ( 2014 ) developed an effective method to increase shoot multiplication in the green gram culture using cotyledonary nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Disinfection with 70% ethanol (60 s) followed by treatment with 25% (v/v) bleach solution for 25 min and 50% (v/v) bleach solution for 15 min resulted in 85% and 80% contamination of in vitro cultures, respectively, and high mortality (80%) of the explants. In contrast, Dar et al (2012) reported 88% survival and no contamination of nodal explants of H. rosa-sinensis collected from an outside garden when surface-disinfected with 50% (v/v) Clorox ® [5.25% (w/v) NaOCl] bleach solution containing a higher concentration (2.63%) of NaOCl. In general, however, microbial contaminations of in vitro cultures are found to occur more readily when the explant source is taken directly from field grown plants (Lobodina et al, 2020).…”
Section: Explant Source and Disinfectionmentioning
confidence: 96%
“…In general, however, microbial contaminations of in vitro cultures are found to occur more readily when the explant source is taken directly from field grown plants (Lobodina et al, 2020). Disinfection of nodal explants is considered to be more difficult since the attachment of the petiole to the stem at an angle creates a V-shaped trough wherein contaminants can be trapped, making it more difficult to sterilize nodal explants with axillary buds (Dar et al, 2012).…”
Section: Explant Source and Disinfectionmentioning
confidence: 99%
“…Sakr et al (2011) reported that surface sterilization with 20% Clorox gave the best result of survival for shoot tips and axillary buds of Cerbera odollam (Apocynaceae). Dar et al (2012) stated that the optimized sterilization conditions for Hibiscus rosa-sinensis node explants were 40% Clorox for 20 min exposure. Dar et al (2012) on Hibiscus rosa-sinensis stated that the optimium sterilization conditions for explants were 40% Clorox-20 min exposure, 10% Clorox-15 min exposure, and 5% Clorox-40 min exposure for the node, internode and shoot tip, respectively.…”
Section: Data Presented Inmentioning
confidence: 99%
“…Dar et al (2012) stated that the optimized sterilization conditions for Hibiscus rosa-sinensis node explants were 40% Clorox for 20 min exposure. Dar et al (2012) on Hibiscus rosa-sinensis stated that the optimium sterilization conditions for explants were 40% Clorox-20 min exposure, 10% Clorox-15 min exposure, and 5% Clorox-40 min exposure for the node, internode and shoot tip, respectively. Abd Alla et al (2013) treated stem nodes of cassava (Manihot esculenta), with different concentrations of Clorox (10, 20 and 30%).…”
Section: Data Presented Inmentioning
confidence: 99%